2019
DOI: 10.1016/j.jimonfin.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The impact of real exchange rate shocks on manufacturing workers: An autopsy from the MORG

Abstract: We study the impact of large real exchange rate shocks on workers in sectors initially more exposed to international trade using the Current Population Survey's (CPS) Merged Outgoing Rotation Group (MORG) from 1979 to 2010 combined with new annual measures of imported inputs, a proxy for offshoring. We find that in periods when US relative prices are high, and imports surge relative to exports, workers in sectors with greater initial exposure to international trade were more likely to be unemployed or exit the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(43 reference statements)
0
4
1
Order By: Relevance
“…The outcome of the findings is in line with the study of Dong, Ma and Wei (2020), and Chang (2011) that reported that exchange rate and employment exert a positive relationship in the literature. While the result contradicts the study by Dai and Xu (2017), Lusher (2019), andDemir (2004) who documented a negative relationship between exchange rate and employment. In the short run, changes in output and trade openness in the manufacturing sector are inelastic to employment while change in the exchange rate is fairly elastic to employment 4 presents the Canonical Co-integrating Regression (CCR) result for output and employment.…”
Section: Source: Authors' Computation Using Eviews 10contrasting
confidence: 77%
See 2 more Smart Citations
“…The outcome of the findings is in line with the study of Dong, Ma and Wei (2020), and Chang (2011) that reported that exchange rate and employment exert a positive relationship in the literature. While the result contradicts the study by Dai and Xu (2017), Lusher (2019), andDemir (2004) who documented a negative relationship between exchange rate and employment. In the short run, changes in output and trade openness in the manufacturing sector are inelastic to employment while change in the exchange rate is fairly elastic to employment 4 presents the Canonical Co-integrating Regression (CCR) result for output and employment.…”
Section: Source: Authors' Computation Using Eviews 10contrasting
confidence: 77%
“…Also in China, Dai and Xu (2017) documented that exchange rate shock resulted in the reallocation of employment across the industries. More so, Campbell and Lusher (2019) reported that exchange rate shock affects workers in the manufacturing sector negatively where there is a high degree of exposure to international trade but reduces wage across in all sectors. Furthermore, the study by Demir (2004) shows that exchange rate shock causes employment reduction in Turkey.…”
Section: Review Of Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we define treatment and control groups on the basis of a worker's industry presanctions level of exposure to international trade. We measure trade exposure at the industry level as the ratio of import penetration to the export share (Campbell and Lusher 2019). We then define treated workers as those employed in industries with above-median levels of trade exposure.…”
Section: Datamentioning
confidence: 99%
“…11 Moreover, we define treatment and control groups on the basis of a worker's industry presanctions level of exposure to international trade. We measure trade exposure at the industry level as the ratio of import penetration to the export share to capture the total effect of the sanctions (Campbell and Lusher 2019). We then define treated workers as those employed in industries with above-median levels of trade exposure.…”
Section: Datamentioning
confidence: 99%